Peran Kesejahteraan Guru Paud Terhadap Produktivitas Kerja Di TK Kota Yogyakarta - Wijaya, Kemala; Wati , Dewi Eko (Buletin Literasi Budaya Sekolah, 2025)
The quality of early childhood education depends on teachers’ productivity, which reflects their effectiveness, and competence in carrying out educational duties such as lesson planning, classroom management, interaction with children, and developmental assessment. This study aims to explore the role of teacher well-being in influencing work productivity among early childhood education teachers in kindergartens across Yogyakarta City. Using a qualitative case study approach, data were collected from both certified and non-certified teachers through in-depth interviews, non-participant observations, and documentation analysis. The validity of the data was ensured through technique triangulation, while data analysis involved data reduction, presentation, and conclusion drawing. The findings revealed that teachers’ physical well-being, including financial fulfillment, health security, and access to learning facilities, contributes to their stability and focus in teaching. Meanwhile, spiritual well-being expressed through supportive work environments and harmonious relationships encourages motivation and creativity. Teacher productivity is also influenced by training, motivation, and collaborative work climates, despite challenges such as limited facilities, changing policies, and communication gaps with parents. Strengthening institutional support and collaboration between schools and parents is essential for sustaining teacher productivity in Yogyakarta kindergartens. This study provides theoretical reinforcment of teacher well being and practical guidance for developing policies to support early childhood teacher productivity.